Calcium and cell function. - Cheung, Wai Yiu (Molecular biology., 1980)
Calcium and Cell Function, Volume I: Calmodulin covers calmodulin-regulated functions. The book discusses the preparation, properties, structure, function, evolution, and structure-function relationships of calmodulin; and calmodulin-dependent adenylate cyclase. The text also describes the transport of calmodulin and plasma membrane calcium; the role of calmodulin and troponin in the regulation of phosphorylase kinase from mammalian skeletal muscle; and calcium-dependent protein phosphorylation in mammalian brain and other tissues. The role of calmodulin in dopaminergic transmission; the immun.